Fitting Markov property to genetic sequences - Židanavičiūtė, Jurgita; Rekašius, Tomas (Lietuvos matematikos rinkinys, 2023)
In this paper DNA sequents are modelled as discrete-state Markov chains. Statistical data is presented in contingency tables form. The generalized logit model is used to test the first-order Markov property for all coding and non-coding subsequences of DNA.
Keywords: contingency tables; generalized logit; Markov chains